Analisis Tingkat Literasi Keuangan Pada Dosen Universitas Telkom Tahun 2016 - Nadya Nadya; Nadya Novandriani Karina Moeliono (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2017)
Financial literacy has a long-term goal for all segments of society, which is to increase literacy someone who previously less literate or not literate become well literate and increase the number of users of products and financial services. Targets for the creation of a society that financial literate is a Housewife, SMEs, Professionals, Students, Student Employees and Pensioners. In 2016 the focus of the Financial Services Authority (OJK) targets are employees including professors. This study was conducted to determine the level of professor’s financial literacy at the Telkom University 2016 by using quantitative descriptive approach, with a proportionate stratified random sampling. The results showed that the level of professor’s financial literacy at the Telkom University in 2016 is still in the low category with a percentage value of 53,1%.